2012
DOI: 10.1038/ejcn.2012.143
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte telomere length and its relation to food and nutrient intake in an elderly population

Abstract: BACKGROUND/OBJECTIVES: Shorter leukocyte telomere length (LTL) is associated with several chronic diseases, but only a few studies have assessed the association between dietary factors and LTL. Our objective was to study the association between fats, fruits, vegetables and LTL in a cross-sectional study design. We hypothesized that intakes of fruits and vegetables would be positively associated with LTL and that intakes of fats, and especially saturated fatty acids (SFAs), would be negatively associated with L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
3
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 51 publications
4
79
3
5
Order By: Relevance
“…Así, la ingesta de grasa total y grasa saturada (y alimentos que las contengan) se refiere a menor LTL (141,142,146,149 de reducir el peso y la ingesta de grasa total y saturada y aumentar la ingesta de fibra dietética y el nivel de actividad física Grupo control: asesoramiento general sobre los beneficios de la reducción de peso, la actividad física y una dieta saludable Edad y sexo: TL relativa correlacionada inversamente con la edad en los dos muestreos de ADN (β = Tabla IV (Cont. ).…”
Section: Resultados Y Discusiónunclassified
See 2 more Smart Citations
“…Así, la ingesta de grasa total y grasa saturada (y alimentos que las contengan) se refiere a menor LTL (141,142,146,149 de reducir el peso y la ingesta de grasa total y saturada y aumentar la ingesta de fibra dietética y el nivel de actividad física Grupo control: asesoramiento general sobre los beneficios de la reducción de peso, la actividad física y una dieta saludable Edad y sexo: TL relativa correlacionada inversamente con la edad en los dos muestreos de ADN (β = Tabla IV (Cont. ).…”
Section: Resultados Y Discusiónunclassified
“…Sin embargo, la mayoría de los estudios que obtuvieron resultados significativos tuvieron mayor calidad en su diseño. Por ejemplo, en tres estudios (145,146,152), la ingesta de vegetales se asoció con telómeros más largos especialmente en mujeres, pero en otros, estos resultados no fueron aprobados (37,42,(140)(141)(142)(143)153,158,165). En dos estudios, la ingesta de grasas y aceites y alimentos que contenían grasa se relacionó negativamente con la TL en las mujeres (142,149).…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…Furthermore, these findings of a beneficial role of MeDi on LTL echo with the findings from a recent intervention study promoting MeDi, which found a higher adherence to the MeDi strengthened the prevention of telomere shortening among carriers of the Ala allele of the peroxisome proliferatoractivated receptor-γ2 (PPARγ2) gene (Garcia-Calzon et al 2014). In line with our observation of an association between vegetable consumption and LTL length, a study of 1942 participants aged 57-70 years from the Helsinki Birth Cohort Study (HBCS) also found that women consuming more vegetables had longer LTL (Tiainen et al 2012). In a case-control study of more than 1600 participants from the Prostate, Lung, Colorectal, and Ovarian (PLCO) Cancer Screening Trial (Mirabello et al 2009), vegetable intake was not associated with LTL, but a healthy lifestyle characterized by higher fruit and vegetable intake, low or no cigarette use, lower BMI, and more physical activity was positively correlated with longer LTL.…”
Section: Discussionmentioning
confidence: 62%
“…Associations between dietary factors and telomere length have also been examined previously. A number of studies have reported eating processed meats, 102,103 and food high in polyunsaturated fats 99 or saturated fatty acids 104 were associated with shorter telomere length, whereas high intake of vegetables and fruits, 105 omega-3 fatty acids, 106 fiber, 99,107 vitamins, 99,[108][109][110][111][112] or Chinese green tea 113 were related to longer telomere length. These observations have led to a belief that the association between depression and telomere length may be moderated in part by dietary factors.…”
Section: Unhealthy Lifestyle Behaviorsmentioning
confidence: 99%